State ownership and market reactions to misconduct announcements of Chinese listed firms: a legitimacy perspective. Issue 1 (31st December 2023) - Hu, Chenhao
Abstract: Announcements of corporate misconduct can trigger negative market reactions. However, our understanding of mechanisms that shape variations of investors' responses across different disclosed-firms is underdeveloped. From the legitimacy theory perspective, this study focuses on the impact of state ownership on market reaction to misconduct announcements. Using a sample of misconduct announcements of Chinese listed firms from 2010 to 2021 and employing a combination of an event study method and a Heckman two-stage model, this study finds that market reaction to misconduct announcements is weaker if state ownership of the disclosed firm is larger. Furthermore, the affiliation level of SOEs (central SOEs versus local SOEs) weakens the positive association between state ownership and market reaction. The main positive effect is strengthened when the disclosed firms are located in regulated industries.